Border Catholic Schools: Unique Stakeholder Alliances (Part II) - Watt, Karen M. (Catholic Education: A Journal of Inquiry and Practice, 2002)
The article presents the results of a qualitative study extracted from the dissertation The Impact of Catholic Schooling on Low-Income Mexican-American Students (Watt, 1999). This study explored four case studies of third-grade teachers, their schools, and their classrooms, in a Hispanic cultural context. Findings revealed that the Border Catholic Schools were communities of consensus with regard to the nature and mission of Catholic schooling. All stakeholders “held the same stake,” agreeing on the curriculum, instruction, and operation of the Border Catholic Schools. Part one of this study was published as “Border Catholic Schools: Unique Stakeholder Alliances (Part 1)” (Watt, 2002) in Volume 6, Number 1.